Infant Feeding Perceptions and Barriers to Exclusive Breastfeeding in Urban and Rural Cameroon - Ngongalah, Lem; Rawlings, Ngwa Niba; Emerson, Wepngong; Titilope, Oluwaniyi; Sharon, Mumah (International Journal of Child Health and Nutrition, 2018)
Background: Child malnutrition is highest in Sub-Saharan Africa. Over 45% of children in Cameroon die each year from malnutrition-related causes, most of which are preventable. Exclusive breastfeeding is a well-acknowledged and cost-effective intervention against malnutrition-related illnesses in children. However, the practice remains low in Cameroon. This study explored perceptions of mothers, care givers and key informants on infant feeding in Cameroon, and barriers to exclusive breastfeeding. Methods: A qualitative methodology was used, comprising key informant interviews and focus group discussions with nursing mothers, grandmothers and health workers; in one urban and one rural area in Cameroon. Participants were selected using convenience, purposive and snowball sampling methods. Data were analysed using thematic analysis. Results: Cameroonian mothers were supportive of breastfeeding. However, knowledge of exclusive breastfeeding and its benefits was poor. Mothers expressed doubts about its feasibility and showed concerns about satisfying their babies’ feeding and health needs. Barriers included factors which either affected women’s abilities to breastfeed or their babies’ satisfaction, family influences, other responsibilities, cultural and societal factors, and lack of support from the healthcare system. Conclusions: This study highlighted a sizeable gap between mothers’ lived experiences and infant feeding recommendations. Living in rural areas was an added disadvantage. Developing effective strategies to increase exclusive breastfeeding rates requires that mothers’ needs be understood and that influencing factors be addressed. Supportive environments are also required to promote and protect the rights and abilities of mothers to breastfeed exclusively.